Laboratory Unit Operations and Experimental Methods in Chemical Engineering - Basha, Omar M.; Morsi, Badie I. (IntechOpen, 2018)
This book covers a wide variety of topics related to the application of experimental methods, in addition to the pedagogy of chemical engineering laboratory unit operations. The purpose of this book is to create a platform for the exchange of different experimental techniques, approaches and lessons, in addition to new ideas and strategies in teaching laboratory unit operations to undergraduate chemical engineering students. It is recommended for instructors and students of chemical engineering and natural sciences who are interested in reading about different experimental setups and techniques, covering a wide range of scales, which can be widely applied to many areas of chemical engineering interest.